Optical vortices generated by a PANDA ring resonator for drug trapping and delivery applications - Suwanpayak, Nathaporn; Jalil, Muhammad Arif; Teeka, Chat; Ali, Jalil; Yupapin, Preecha P. (My University, 2011)
We propose a novel drug delivery system (DDS) by using a PANDA ring resonator to form, transmit and receive the microscopic volume by controlling some suitable ring parameters. The optical vortices (gradient optical field/well) can be generated and used to form the trapping tool in the same way as the optical tweezers. The microscopic volume (drug) can be trapped and moved (transported) dynamically within the wavelength router or network. In principle, the trapping force is formed by the combination between the gradient field and scattering photons, which has been reviewed. The advantage of the proposed system is that a transmitter and receiver can be formed within the same system, which is called transceiver, in which the use of such a system for microscopic volume (drug volume) trapping and transportation (delivery) can be realized. © 2010 Optical Society of America.